Proposal to Use of the Websocket Protocol for Web Device Control - Maia, Adriano de Oliveira; Silva, Danilo Avilar (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
The Websocket protocol enables a full-duplex communication, besides it simplifies an exchange of data and reduces network overload. This paper proposes the use of the Websocket protocol in control and service devices through web within real-time requirements. Through tests made in a virtual environment and another one in embedded experiment, It is possible to validate an initial proposal of implementation the Websocket protocol. From the analysis of the results obtained, it can be seen the use of the proposal in question provides a considerable reduction in the quantity of requests and transferred data in relation to traditional approach to sending data in HTTP-based communications. Consequently it seems to be a very promising technique for this type of application.